Utilisation of Eucalyptus Hybrid-a Review - Rajput, S. S.; Tewari, M. C. (Indian Forester, 1984)
Eucalyptus terelieorni popularly known as Eucalyptus hybrid or Mysore gum has been plated extensively throughout India under the plantation programmes in the successive five year plans. Although most of the plantations have been raised for pulp and paper for which the species provides an excellent raw material, the question are often posed about its suitability for other purposes. In order to determine its suitability for varied purposes, investigations have been recently undertaken and several are underway at Forest Research Institute, Dehra Dun. The results of these studies have been reviewed in the present paper. On the basis of physical and mechanical properties, E. tereticornis has been found to be 10% heavier, 15% harder and 15% higher in shock resisting ability in comparison to teak. However, it has heen found to be 25% weaker than teak in strength. Under machining operations, it has been found that this species can be very well machine planed, turned, bored or mortised. The working quality index of E. tereticornis has been found to be 94 with teak as 100. The studies on seasoning, durability and treatability behaviour are in progress. However, the results obtained so far indicate that it can be seasoned well with suitable modification in sawing techniques as well as with preseasoning chemical treatment The species belongs to non-durable and non-treatable class with proper care E. tereticornis can be used for making simple as well as bentwood furniture, tool handles, pallets and many other items. By proper selection the species can he used for overhead power and telecommunication line poles, it is already well known that, the eucalypts yield excellent raw material for pulp and paper. Some trees of E. teretlcornls yield Cineole rich medicinal oil. The bark of E. tereticornis can be used for producing oxalic acid and can also be used for making hardboard. Plywood has also been developed from the species but the results are not very encouraging. Many studies are underway to find still more and more uses of Eucalyptus tereticornis and the results will be available In the near future.